Pre-treatment thrombocytosis and ovarian cancer survival: A meta-analysis - Vasilios Pergialiotis; Lito Vogiatzi Vokotopoulou; Dimitrios-Efthymios Vlachos; Michalis Liontos; Emmanuel Kontomanolis; Nikolaos Thomakos (Elsevier, 2024)
An association between thrombocytosis and cancer progression and decreased survival has been observed for various forms of cancer. The aim of this study was to evaluate the impact of pre-treatment thrombocytosis on ovarian cancer survival. Medline, Scopus, Clinicaltrials.gov, Cochrane Central Register of Controlled Trials CENTRAL and Google Scholar were searched systematically for studies that compared survival outcomes of patients with ovarian cancer who had pre-treatment thrombocytosis with survival outcomes of patients with normal platelet counts. Fourteen articles were retrieved, with a total of 5414 patients with ovarian cancer. The methodological quality of included studies ranged between moderate and high. Patients with advanced stage disease were more likely to have pre-treatment thrombocytosis, and this was associated with lower rates of optimal debulking. Thrombocytosis was also associated with increased likelihood of recurrence of ovarian cancer [hazard ratio (HR) 2.01, 95 % confidence interval (CI) 1.34-3.01] and increased risk of death from ovarian cancer (HR 2.29, 95 % CI 1.35-3.90). The incidence of deep vein thrombosis was comparable in both groups (odds ratio 1.62, 95 % CI 0.48-5.46). Considering these findings, it is evident that pre-treatment thrombocytosis in patients with ovarian cancer is associated with increased risk of recurrence and death. Pre-treatment thrombocytosis is a potential sign of advanced stage disease, and may be predictive of suboptimal tumour debulking during surgery. Its association with other factors that affect survival, including platinum resistance and response to targeted therapy, remains poorly explored, although preliminary data suggest a potential correlation.